Organizational culture, attitudes and behaviors that favor the organization. Case Universidad Autónoma de Tamaulipas - Sánchez-Saavedra, Jimena (2023)
The behaviors and attitudes that favor performance in an organization are the cause of its success, such is the case of the Autonomous University of Tamaulipas (UAT). A qualitative study was used in which the perceptions of the collaborators regarding the behaviors that can be presented in the organizational culture were analyzed, through a dichotomous response survey with an adaptation of the factors proposed in the Organizational Normative Behavior Questionnaire. As a result, it was obtained that the behaviors in the organizational culture at the Autonomous University of Tamaulipas (UAT) favor the performance of its collaborators and are present in more than 70% of the population. It is concluded that the factors quality, collaboration, consideration, orientation to authority and competition are above the threshold of 70% established.